Buyer differences in supplier development program implementation with local suppliers: Case study in the Malaysian automotive industry - Abdul Kadir, Kadzrina; Ali, Hassan (2013)
Supply chain management focuses on improving the performance of the supplier.Through supplier development programs, buyers develop supplier’ capability, improving suppliers’ performance.Through interviews, this research focus on how buyers differ in implementation of supplier development programs and why, from the viewpoints of the suppliers.